Optimisation of titanium-hydroxyapatite composites using bioactive glass for fabrication of functionally graded dental posts / Mohamed Abdulmunem Abdulateef - Mohamed Abdulmunem, Abdulateef (2019)
Optimisation of the chemical, physical and mechanical properties of Titanium-hydroxyapatite (Ti-HA) composites using various ratios of bioactive glass to fabricate a functionally graded dental posts (FGDPs). Bioactive glass (BG) (containing SiO2, NaO, CaO, B2O3, P2O5, CaF2, MgO, TiO2) was prepared and added in three different ratios (5%, 10%, and 15%) to five different Ti-HA composites. Section 1; mixtures were prepared, milled, pressed, sintered and visually checked. In section 2; the optimum ratio of bioactive glass was selected according to section 1 results and was then added to the Ti-HA composites and divided into two groups, each containing five layers. Samples in Group 1 were sintered with an air atmosphere furnace, while samples in Group 2 were sintered with a vacuum furnace and then all groups were tested with XRD and EDX. Density, micro-hardness, modulus of elasticity and compression strength was also measured. Section 3; based on the results in part 2, functionally graded dental posts (FGDPs) were then fabricated. Section 4; FGDPs and other post types were restored in endodontically treated teeth with 10 teeth in each group. Fracture resistance and failure modes were evaluated using a universal testing machine and stereomicroscope and data were analysed using one-way ANOVA and Chi-square tests. Section 5; stress distributions were also evaluated using teeth models restored with the FGDPs, titanium, fibre, and stainless steel posts and analysed using finite element analysis. Ti-HA composites that were incorporated with a 10% ratio of BG were stable and crack free when compared to other groups. In the second section, samples sintered in Group 1 (air atmosphere furnace) showed a significant difference (p= 0.000) as compared to Group 2 (vacuum furnace), in terms of compression strength, micro-hardness values density and modulus of elasticity. In terms of XRD analysis, Group 1 also showed that major phases iv belonged to Ti and HA, and a minimum amount of Ti was oxidised to Ti2O. Whereas, in Group 2; the main phases belonged to Ti and HA, and the minor phases showed that HA had decomposed into TCP and TTCP. EDX also showed that there was no contamination recorded in both groups. In terms of fracture resistance, FGDPS and titanium groups showed a higher fracture resistance compared to the stainless steel group (p= 0.000 and p= 0.032, respectively). In terms of failure modes, FGDPs group also showed higher restorable failures than other groups, followed by the fibre group. In terms of stress distribution, regardless of load direction, maximum stress was concentrated at the core-crown interface in the coronal third of the crown, and was the highest in fibre and FGDPS models, resulting in restorable failures. 10% BG was the most suitable ratio to be added to Ti- HA composites compared to other ratios. Sintering Ti-HA-BG composites using air atmosphere furnace resulted in better chemical, physical and mechanical properties compared to those sintered in vacuumed furnace. It was found that teeth restored with FGDPs and titanium posts showed a higher fracture resistance than those restored with stainless steel posts. Failure modes tended to be more restorable with teeth restored with FGDPs than those restored with other types of dental post. Stress distribution was uniformly distributed in FGDPs and fibre models as compared to titanium and stainless steel models.